1990
DOI: 10.1093/oxfordjournals.jbchem.a123294
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence of the Gene Coding for Four Subunits of Cytochrome c Oxidase from the Thermophilic Bacterium PS31

Abstract: The gene coding for four subunits of cytochrome aa3-type oxidase was isolated from a genomic DNA library of the thermophilic bacterium PS3 and sequenced. The N-terminus of each subunit was also sequenced to verify the initiation site of the reading frame. The deduced amino acid sequences contained 615 amino acid residues for subunit I (CO1/caaB product), 333 residues for subunit II (CO2/caaA product), 207 residues for subunit III (CO3/caaC product), and 109 residues for subunit IV (CO4/caaD product) after proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The cleaved site, -M-A-G-C-, fits the signal-sequence motif of lipoproteins, -L\M-A\S-G-C-, and is similar to those of the subunits II of other oxidases (Ishizuka et al, 1990 ;Quirk et al, 1993 ;Ma et al, 1997 ;Bengtsson et al, 1999). It was empirically demonstrated that the thiol group is diacylglycerated in the caa $ -type cytochrome c oxidase from B. subtilis and the bo $ -type quinol oxidase from Escherichia coli.…”
Section: Structural Features Of Subunit IImentioning
confidence: 57%
“…The cleaved site, -M-A-G-C-, fits the signal-sequence motif of lipoproteins, -L\M-A\S-G-C-, and is similar to those of the subunits II of other oxidases (Ishizuka et al, 1990 ;Quirk et al, 1993 ;Ma et al, 1997 ;Bengtsson et al, 1999). It was empirically demonstrated that the thiol group is diacylglycerated in the caa $ -type cytochrome c oxidase from B. subtilis and the bo $ -type quinol oxidase from Escherichia coli.…”
Section: Structural Features Of Subunit IImentioning
confidence: 57%
“…32 ) PS3,26) and Saccharomyces cerevisiae,27) respectively. The deduced amino acid sequences of the ubiA product and COQ2 are from this study and Alexander Tzagoloff et al, 11) respectively.…”
Section: The Ubia-iacz and Ubic-iacz Fusion And Their Expressionmentioning
confidence: 99%
“…The homologous bacterial oxidases were originally thought to contain only two subunits (COI and COIl), but COII or its gene has been recently found in a number of species (for a review, see Saraste, 1990). COIl is thus likely to be a universal part of all aa3-type oxidases (Haltia et al, 1988;Buse et al, 1989;Ishizuka et al 1990; Saraste et al, 1991). Moreover, a homologous protein is present in the cytochrome o terminal oxidase complex of Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%